Implementation of Technology-Based Learning Media for Teachers at Leading Schools in Limbangan District - Nasrulloh, Iman; Nugraha, Wildan; Herdiana, Dodi (Fakultas Kewirausahaan Universitas Garut, 2023)
In this context, Limbangan, as a district focused on superior education, needs to ensure that teachers have adequate access to and understanding of the use of technology in the teaching and learning process. Since the COVID-19 pandemic, many schools have shifted to online learning, forcing teachers to rapidly adapt their teaching methods. The community service method for this project is designed to deliver and implement technology-based learning media for teachers in superior schools in Limbangan District. This method is descriptive, encompassing various structured steps to achieve the objectives of this community service. The following is a detailed section of the method used. In a survey, students felt more motivated and interested in learning when technology was used in their lessons. This indicates that technology not only benefits teachers but also positively impacts the student learning experience. This skill improvement aligns with research findings showing that appropriate training interventions can optimize teachers' mastery of technology. Therefore, ongoing training should be considered an integral part of teachers' future professional development.